(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2015)
Chikungunya is an acute febrile illness caused by chikungunya virus (CHIKV). In this study, theÂ envelope E1 gene of CHIKV was cloned and expressed in a baculovirus system. TheÂ recombinant E1 protein with N-term 6-His residues protein was successfully expressed andÂ purified as confirmed by SDS-PAGE and western blot analysis. The seroreactivity of theÂ recombinant protein was evaluated in immunoassay for anti-CHIKV IgM and IgG antibodies.Â The recombinant antigen showed 69% sensitivity and 100% specificity for anti-CHIKV IgG byÂ dot blot assay. Detection of anti-CHIKV IgM by dot assay showed 79% sensitivity and 100%Â specificity. No cross reactivity of the antigen was observed with anti-dengue virus serumÂ samples. The results strongly support that the recombinant E1 protein has potential to be used asÂ diagnostic antigen. The used of the antigen in a dot blot assay gives an advantage for laboratoryÂ detection without the need of any specialised equipment.